BUDAYA ORGANISASI DAN PENGELOLAAN SUMBER DAYA MANUSIA TERHADAP PENCAPAIAN TARGET RETRIBUSI PEMOTONGAN DI UPT RUMAH POTONG HEWAN - Anis Ardi, Muhamad; Iskandar, Abubakar; Suarman Sudarsa, Agus (Universitas Djuanda, 2022)
The Technical Implementation Unit of the Animal Slaughtering House is an organizational unit within the Department of Fisheries and Animal Husbandry in Bogor Regency that has an annual levy target for its slaughtering service. This research aims to investigate the impact of organizational culture on achieving the cutting levy target, ascertain the influence of human resource management on achieving the cutting levy target, and determine the relationship between organizational culture, human resource management, and the achievement of the cutting levy target. A sample of 39 respondents was taken from the Technical Implementation Unit of the Animal Slaughtering House, and data were collected through the distribution of questionnaires. The data were analyzed using path modeling, path analysis, and respondent opinion analysis. The results of the research show that the correlation coefficient for organizational culture and the achievement of the cutting levy target is 0.400, indicating a moderate correlation. The correlation coefficient for human resource management and the achievement of the cutting levy target is 0.958, indicating a very strong correlation. However, organizational culture and human resource management do not have a relationship with the achievement of the cutting levy target for animals. This is because for organizational culture, the calculated t-value is less than the table t-value (1.984 < 2.028), while for human resource management, the calculated t-value is greater than the table t-value (19.392 > 2.028).